PR Interval as a Valuable Predictor of Tilt Table Test Results in Patients With Neurally Mediated Syncope - Mohammad Hossein Nikoo; Roozbeh Narimani‐Javid; Alireza Kamrava; Sasan Shafiei; Salma Nozhat; Hosein Fatemian; Ali Asadzadeh; Mehdi Motahari Moadab; Fatemeh Ghanbari; Alireza Arzhangzadeh (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Neurally mediated syncope (NMS) is the primary cause of temporary and self‐limiting loss of consciousness. The tilt table test (TTT) has been consistently employed as a supplementary diagnostic tool for syncope evaluation. However, TTT requires specialized equipment, which is lacking in several emergency room and clinic environments. We hypothesized that patients susceptible to NMS may have higher parasympathetic tone. Thus, this study investigates the correlation between PR interval and Herat rate variability parameters as indicators of parasympathetic tone and TTT results. Methods We included 213 patients referred to our cardiology clinic with an impression of NMS in 2022 and 2023. Data was retrospectively collected from 24‐h ambulatory electrocardiographic monitoring recordings, TTT results, and patients' history and physical examination records. Results The analysis of the PR interval revealed a mean duration of 155 ms (95% CI: 148.61, 161.39) in negative TTT patients and 164.21 ms (95% CI: 158.44, 169.97) in positive TTT patients, indicating a statistically significant difference between two groups (p = 0.035). We also found that patients with a PR interval duration exceeding 160 ms demonstrated a significantly higher prevalence of positive TTT compared to those with a PR interval duration of less than 160 ms (p < 0.001, OR: 3.911, 95% CI: 2.143, 7.140). Conclusions Our study suggests a PR interval longer than 160 milliseconds as a valuable tool for predicting TTT results and identifying patients at higher risk of NMS.